2018 9th ESA Workshop on Satellite NavigationTechnologies and European Workshop on GNSS Signals and Signal Processing (NAVITEC) 2018
DOI: 10.1109/navitec.2018.8642666
|View full text |Cite
|
Sign up to set email alerts
|

Measured GPS performance under LTE-M in-device interference

Abstract: In this paper we present the measurement results for time-to-fix, position accuracy, and carrier-to-noise ratio of commercial Global Positioning System (GPS) receivers under the in-device interference from an LTE-M transmitter. The laboratory measurement set-up is built using software-defined radio (SDR) platforms to conductively feed emulated GPS L1 signals and LTE-M interference signals to the antenna input of the GPS receivers. The LTE-M interference from second harmonics is accurately modelled taking into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The research described in [ 34 , 35 ] indicate that a transmitter transmitting an interfering signal with a power of 244 mW, in a bandwidth of 2 MHz, is sufficient to prevent the reception of GPS signals within a radius of more than 6 km when the receiver is tuned to signals from satellites and within a radius of more than 8 km when the receiver is not yet synchronized with them.…”
Section: Simulation Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The research described in [ 34 , 35 ] indicate that a transmitter transmitting an interfering signal with a power of 244 mW, in a bandwidth of 2 MHz, is sufficient to prevent the reception of GPS signals within a radius of more than 6 km when the receiver is tuned to signals from satellites and within a radius of more than 8 km when the receiver is not yet synchronized with them.…”
Section: Simulation Studiesmentioning
confidence: 99%
“…The research described in [ 34 , 35 ] has also shown that strong interference outside the GNSS systems band may also have a negative impact on the quality of reception of navigation signals. The algorithms that are used to calculate the ratio of the carrier wave power to the spectral power density of the noise make it possible to make a measurable assessment of the quality of the received signals.…”
Section: Simulation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The long term evaluation (LTE) signal proposed by Light Square was rejected by the Federal Communications Commission (FCC) due to the severe performance degradation of various GPS receivers in real tests [2]. The influence of the third harmonics of DVB-T signals on GPS L1/Galileo E1 was also tested with the carrier to noise ratio (CNR) as an evaluation indicator [3]. The impact of LTE-machine to machine (LTE-M) second harmonics on GPS receivers was also evaluated in terms of its positioning error and CNR reduction.…”
Section: Introductionmentioning
confidence: 99%